Interlocutions on Mental Health and Work: he Experience of Extension in The UFJF Medicine Course - de Miranda Ramos, Andréia Aparecida; Trevisan Zorzetto, Luis Henrique; Viana Costa, Amanda; de Oliveira Mota, Ana Carolina; Souza Silva, Caroline (Guará Journal, 2018)
The  main  purpose  of  the  project  is  to  address issues of  mental  health  related  to  work  and  support patients  with  work-related  mental  disorders. It is carried  out  at  the  Regional  Reference  Center  on Occupational  Health  of  Juiz  de  Fora  /  MG  and  UFJF Medical  School.  Support  and  study groups are held monthly. The participants voluntarily register and are coordinated by medical students and the coordinator of the Project. All  participants  in  the  support  group  are transport  workers  diagnosed  with  work-related mental  illness  and  associated  orthopedic  diseases.  In the  study  group,  the  integration  of  professionals  and students  from  different institutions takes place. Vignettes have been created on a radio program,  in partnership  between  patients  and  the  UFJF  medical students.  The  groups  have  shown  important  space for  understanding  the  process of mental illness and work, allowing the creation of new coping strategies as well as there has been a participation of participants in the group.
Keywords: Work ́s health; Mental health; Extension activies